1991
DOI: 10.1063/1.349644
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary scattering in CuInSe2 films

Abstract: Electrical conductivity and Hall mobility of CuInSez films were measured in the temperature range of 77-400 K. The films were deposited with different Cu/In ratios ranging from 0.7-0.9 and at substrate temperatures of 620-720 K. Effects of grain boundary scattering on the electron transport properties were studied carefully and it was observed that scattering at the grain boundaries is a predominant factor controlling the electron transport properties at lower temperatures while complex scattering mechanisms b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The electrical properties strongly depend on the densification and grain size. The carrier scattering at the pores or grain boundaries is a predominant factor in controlling the electrical properties of CIGS . The CIGS density increased with increasing submicron‐sized particle addition, leading to the reduction of carrier scattering from the pores and hence increasing the Hall mobility.…”
Section: Resultsmentioning
confidence: 88%
“…The electrical properties strongly depend on the densification and grain size. The carrier scattering at the pores or grain boundaries is a predominant factor in controlling the electrical properties of CIGS . The CIGS density increased with increasing submicron‐sized particle addition, leading to the reduction of carrier scattering from the pores and hence increasing the Hall mobility.…”
Section: Resultsmentioning
confidence: 88%
“…The most important sources of scattering in typical semiconductor materials include (a) boundary scattering from pores or grain boundaries, (b) activation barrier at grain boundaries, (c) local strain field, or (d) ionized impurity scattering [19]. Sanyal et al [20] investigated the electrical conductivity and Hall mobility measurements on CIS films and observed that scattering at the grain boundaries is a predominant factor in controlling the electron transport properties at low temperatures. The density and grain size of CIGS increased with increasing soaking time at 550 1C, which led to the reduction of carrier scattering from the grain boundaries and pores and hence increasing the Hall mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The most important sources of scattering in typical semiconductor materials include (a) boundary scattering from pores or grain boundaries, (b) activation barrier at grain boundaries, (c) local strain field, or (d) ionized impurity scattering . Sanyal et al investigated the electrical conductivity and Hall mobility measurements on CIS films and observed that scattering at the pores or grain boundaries is a predominant factor in controlling the electron transport properties at low temperatures. The pre‐sintered and selenized film exhibited higher density and larger grain size, which led to carrier scattering reduction from the pores and grain boundaries and hence increased the Hall mobility.…”
Section: Resultsmentioning
confidence: 99%